Shiga toxin-producing Escherichia coli in healthy young beef steers from Argentina: prevalence and virulence properties - Meichtri, Lelis (2004)
Fil: Meichtri, Lelis. Instituto Tecnologı́a de Alimentos, Centro de Investigación de Agroindustria, Instituto Nacional de Tecnologı́a Agropecuaria, Argentina, C.C. 77. C.P. (B1708WAB), Morón, Buenos Aires; Argentina.